Levothyroxine Supplementation in Euthyroid Pregnant Women With Positive Autoantibodies: A Systematic Review and Meta-Analysis - Di Girolamo, Raffaella; Liberati, Marco; Silvi, Claudia; D’Antonio, Francesco (Frontiers in Endocrinology, 2022)
Objectives: To explore the role of levothyroxine (LT4) supplementation in in affecting the outcome in pregnant euthyroid women with thyroperoxidase (TPO) antibodies. Methods: MEDLINE, EMBASE, Google Scholar and the Web of Science databases were searched. The primary outcome explored was pre-term birth (PTB), defines as live birth before 37 completed weeks of gestation. The secondary outcomes explored were gestational hypertension, pre-eclampsia (PE), placental abruption, miscarriage, defined as the loss of an embryo or fetus before the 20th week of pregnancy, intra-uterine death (IUD), admission to neonatal intensive care unit (NICU). All these outcomes were explored in the euthyroid women with TPO antibodies receiving compared to those not receiving LT4 supplementation in pregnancy. Quality assessment of the included studies was assessed using the Revised Cochrane risk-of-bias tool for randomized trials (RoB 2) and the Newcastle-Ottawa Scale (NOS) for case-control studies. Head-to-head meta-analyses using random-effect model were used to analyze the data and results reported as pooled odd ratios (OR) with their 95% confidence intervals (CI). Results: When considering RCTs and observational studies together, the risk of PTB was lower in TPO positive women with normal thyroid function with an OR of 0.60 (95% CI 0.4-0.9). This association between LT4 supplementation and reduced risk of PTB came mainly from observational studies (OR: 0.29, 95% CI 0.1-0), while RCTs did not show any beneficial effect of LT4 supplementation in affecting this outcome). There was no difference in the risk of gestational hypertension, preeclampsia, placental abruption, miscarriage, and admission to NICU between the two groups in the pooled analysis. Conclusions: LT4 supplementation in TPO euthyroid women is not associated with a reduced risk of PTB in TPO positive women with normal thyroid function. However, the small number of included cases and dissimilarity in inclusion criteria, therapeutic strategies and populations analyzed highlights the need for properly designed RCTs to elucidate whether treatment with LT4 may reduce the risk of adverse obstetric outcomes in these women.